Physi-chemical and sorption properties of biochars prepared from peanut shell using thermal pyrolysis and microwave irradiation. (August 2017) - Chu, Gang; Zhao, Jing; Chen, Fangyuan; Dong, Xudong; Zhou, Dandan; Liang, Ni; Wu, Min; Pan, Bo; Steinberg, Christian E.W.
Abstract: Microwave irradiation (MW) is an effective technique in heating and pyrolysis. This study compared the properties of peanut shell-biochars produced using MW and muffle furnace (FN). At the same pyrolysis temperature, MW biochars preserved more biomass (as indicated by their higher yields and higher abundance of functional groups) and possessed larger surface areas due to the high abundance of micropores. MW biochars generally exhibited higher adsorption of carbamazepine (CBZ) and bisphenol A (BPA) than FN biochars. However, their surface area-normalized sorption was lower, suggesting that the inner pores may not be fully available to CBZ and BPA sorption. We observed significant free radical signals in both types of biochars. Although CBZ and BPA did not degrade in the biochar sorption systems, the potential role of stronger free radical signals in MW biochars for organic contaminant control may not be overlooked in studies with other chemicals. Graphical abstract: Highlights: Biochars were prepared through MW and FN and their properties were compared. MW biochars have larger surface areas, more micropores, and higher yield. MW biochars show higher sorption to carbamazepine and bisphenol A. Stronger EPR signals and less g factor variation were observed in MW biochars.